Pseudoaneurysm of profunda femoris artery: a rare complication after intramedullary fixation for an intertrochanteric femur fracture - Jain, Vicky T.; Katariya, Jeetendra; Archik, Shreedhar (International Journal of Research in Orthopaedics, 2019)
Intertrochanteric fracture fixation with a trochanteric femoral nail rarely leads to any vascular or neurological complications. The aim of this case report is to identify a patient with post-operative Pseudoaneurysm of profunda femoris artery and how to manage it. We report a case of 79-year-old male who developed a Pseudoaneurysm of the profunda femoris artery 3 days after intramedullary femoral nailing for a intertrochanteric femur fracture. Percutaneous embolization was performed with subsequent resolution of the symptoms. Diagnosis of vascular complications after hip surgery may be very challenging because symptoms are often nonspecific. Despite their rarity, it is important to know this type of complications to address the diagnostic pathway in the right direction and to treat them promptly.